2012
DOI: 10.1016/j.jchromb.2011.07.021
|View full text |Cite
|
Sign up to set email alerts
|

A high-throughput U-HPLC–MS/MS assay for the quantification of mycophenolic acid and its major metabolites mycophenolic acid glucuronide and mycophenolic acid acyl-glucuronide in human plasma and urine

Abstract: Mycophenolic acid (MPA) is used as an immunosuppressant after organ transplantation and for the treatment of immune diseases. There is increasing evidence that therapeutic drug monitoring and plasma concentration-guided dose adjustments are beneficial for patients to maintain immunosuppressive efficacy and to avoid toxicity. The major MPA metabolite that can be found in high concentrations in plasma is MPA glucuronide (MPAG). A metabolite usually present at lower concentrations, MPA acyl-glucuronide (AcMPAG), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 28 publications
1
29
0
1
Order By: Relevance
“…Also, it was shown that MPAG-free after storage beyond 6 months at À80°C would have a tendency to degrade as a function of time (Figurski et al, 2009). The urinary stability of MPAG and AcMPAG has also been raised as a key issue during the validation work of Klepacki et al (2012. During the first 24 h of storage both MPAG and AcMPAG were stable in urine; however, beyond 24 h there was degradation evident for MPAG and AcMPAG in urine such that by 7 days of storage there was a complete degradation of AcMPAG in urine, while there was a 70% degradation of MPAG in urine (Klepacki et al, 2012). In this report, instability of both analytes also occurred in plasma samples during storage, although the extent of degradation did not appear to be severe (Klepacki et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Also, it was shown that MPAG-free after storage beyond 6 months at À80°C would have a tendency to degrade as a function of time (Figurski et al, 2009). The urinary stability of MPAG and AcMPAG has also been raised as a key issue during the validation work of Klepacki et al (2012. During the first 24 h of storage both MPAG and AcMPAG were stable in urine; however, beyond 24 h there was degradation evident for MPAG and AcMPAG in urine such that by 7 days of storage there was a complete degradation of AcMPAG in urine, while there was a 70% degradation of MPAG in urine (Klepacki et al, 2012). In this report, instability of both analytes also occurred in plasma samples during storage, although the extent of degradation did not appear to be severe (Klepacki et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Several assays have been reported for the analysis of MPA and its metabolites by LC-MS/MS in different matrices (Benech et al, 2007;Brandhorst et al, 2006;Delavenne et al, 2011;Heinig et al, 2010;Kawanishi et al, 2015;Klepacki et al, 2012;Kuhn et al, 2009;Laverdiere et al, 2012;Md Dom et al, 2014;Shen et al, 2009;Upadhyay et al, 2014;Wiesen et al, 2012). However, relatively few assays are available for simultaneous quantification of MPA and its glucuronide metabolites with sufficient sensitivity for AcMPAG, which has a relatively low abundance in comparison with MPAG.…”
Section: Introductionmentioning
confidence: 99%
“…The incorporation of a chip‐based high‐field asymmetric waveform ion mobility spectrometry (FAIMS) separation in the ultra (high)‐performance liquid chromatography–high resolution mass spectrometry (UHPLC–HRMS) for determination of the ( R / S ) ibuprofen 1‐ O ‐acyl glucuronide metabolite in urine has also been reported (Smith et al, ). Analytical methods for acyl glucuronide metabolites quantitation are listed in Table (Klepacki et al, ; Surendradoss et al, ; Liu & Smith, ; Luigi et al, ; Mano et al, ; Merrigan, Kish‐Trier, Seegmiller, & Johnson‐Davis, ; Qiang & Zhang, ; Schwartz, Desai, Bi, Miller, & Matuszewski, ; Smith et al, ; Zhou et al, ).…”
Section: Sample Processingmentioning
confidence: 99%